The high energy X-ray probe (HEX-P): the future of hard X-ray dual AGN science - Pfeifle, Ryan W.; Boorman, Peter G.; Weaver, Kimberly A.; Buchner, Johannes; Civano, Francesca; Madsen, Kristin; Stern, Daniel; Torres-Albà, Núria; Nardini, Emanuele; Ricci, Claudio; Marchesi, Stefano; Ballantyne, D. R.; et al. (Frontiers in Astronomy and Space Sciences, 2024)
A fundamental goal of modern-day astrophysics is to understand the connection between supermassive black hole (SMBH) growth and galaxy evolution. Merging galaxies offer one of the most dramatic channels for galaxy evolution known, capable of driving inflows of gas into galactic nuclei, potentially fueling both star formation and central SMBH activity. Dual active galactic nuclei (dual AGNs) in late-stage mergers with nuclear pair separations < 10 kpc are thus ideal candidates to study SMBH growth along the merger sequence since they coincide with the most transformative period for galaxies. However, dual AGNs can be extremely difficult to confirm and study. Hard X-ray (> 10 keV) studies offer a relatively contamination-free tool for probing 1 Pfeifle et al.the dense obscuring environments predicted to surround the majority of dual AGN in late-stage mergers. To date, only a handful of the brightest and closest systems have been studied at these energies due to the demanding instrumental requirements involved. We demonstrate the unique capabilities of HEX-P to spatially resolve the soft and -for the first time -hard X-ray counterparts of closely-separated (∼ 2 ′′ -5 ′′ ) dual AGNs in the local Universe. By incorporating physically-motivated obscuration models, we reproduce realistic broadband X-ray spectra expected for deeply embedded accreting SMBHs. Hard X-ray spatially resolved observations of dual AGNs -accessible only to HEX-P -will hence transform our understanding of dual AGN in the nearby Universe.